Possible Selves Mapping: Life-Career Exploration With Young Adolescents - Shepard, Blythe; Marshall, Anne (Canadian Journal of Counselling and Psychotherapy, 2007)
Possible selves are cognitive manifestations of goals, aspirations, values, and fears. Although relevant to adolescents' exploration of future personal and career roles, most research and practical application involving possible selves has been with adults. An interview called the Possible Selves Mapping Interview (PSMI) was developed and employed with 42 young adolescents aged 11 to 13. All participants generated at least two hoped-for and two feared selves. Occupational hoped-for and safety feared selves were the most prevalent themes. Only a few gender differences were noted. Implications for counsellors are discussed, including the use of possible selves mapping in personal and career counselling.